Rasionalitas Keputusan Bertahan Ojek Pangkalan dengan Adanya Ojek Online di Stasiun Balapan Kota Surakarta - Anggraeni, Elli Rizki; Trinugraha, Yosafat Hermawan (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This research analyzes rational choice among traditional motorcycle taxi drivers at Balapan Station, Surakarta City. This study employs a descriptive qualitative approach with a single case study based on James Coleman's rational choice theory, focusing on the micro level of actors and resources, as well as supporting three indicators of collective behavior, norms, and corporate actors to explain the phenomena at a macro level. Data was obtained through observation, interviews, and document studies. The findings suggest that actors leverage their ownership of resources to survive within the conventional system amidst the rise of online motorcycle taxi services. The resources held by actors include physical health conditions, ownership of motor vehicles, the location of their base, and loyal customers. Traditional motorcycle taxi drivers also consider economic value, flexibility, and comfort of work, as well as solidarity value, as preferences. Base motorcycle taxi drivers implement several steps as a strategy in facing the development of online motorcycle taxis. The adaptation employed out by traditional motorcycle taxi drivers includes promotions, price adjustments, and the use of Whatsapp application to enhace services.In a macro analysis, collective behavior arises because actors have similarities in actions, norms as a means of control, and corporate actors of the base motorcycle taxi association at Balapan Station.